2013
DOI: 10.1111/jeb.12271
|View full text |Cite
|
Sign up to set email alerts
|

Maternal investment increases with altitude in a frog on the Tibetan Plateau

Abstract: Reproducing females can allocate energy between the production of eggs or offspring of different size or number, both of which can strongly influence fitness. The physical capacity to store developing offspring imposes constraints on maximum clutch volume, but individual females and populations can trade off whether more or fewer eggs or offspring are produced, and their relative sizes. Harsh environments are likely to select for larger egg or offspring size, and many vertebrate populations compensate for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Although we do not have data on offspring survival or condition in high‐elevation species, increased investment in eggs with elevation has been reported across a wide variety of taxa lacking post‐hatching parental care; for example, frogs and snails breeding at high elevations lay larger eggs relative to body size and have increased reproductive investment per egg, respectively (Berven ; Baur & Raboud ; Chen et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Although we do not have data on offspring survival or condition in high‐elevation species, increased investment in eggs with elevation has been reported across a wide variety of taxa lacking post‐hatching parental care; for example, frogs and snails breeding at high elevations lay larger eggs relative to body size and have increased reproductive investment per egg, respectively (Berven ; Baur & Raboud ; Chen et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the morphological variation we observed between Daphnia populations from the Qinghai-Tibetan Plateau and those from lowland China might be due to phenotypic plasticity in response to the different environmental conditions, such as temperature and predator pressures. Alternatively, the different morphology of high altitude D. magna populations, when compared with those from lowland China, might be due to the unique geographical and environmental conditions there (e.g., Chen et al, 2013;Lin et al, 2008). Individual D. magna with longer heads, wider and longer bodies are more likely to survive and reproduce in the harsher environments (i.e., extremely low temperature and strong ultraviolet radiation) of the Qinghai-Tibetan Plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Individual D. magna with longer heads, wider and longer bodies are more likely to survive and reproduce in the harsher environments (i.e., extremely low temperature and strong ultraviolet radiation) of the Qinghai-Tibetan Plateau. Indeed, the frog Rana kukunoris Xie, 2000 in the Qinghai-Tibetan Plateau produces larger eggs than do those from the lowlands, which allows for increased rates of embryonic development leading to earlier hatching of tadpoles (Chen et al, 2013). The larger females of R. kukunoris in high-altitude habitats produce more gelatinous matrix surrounding the eggs, which could protect embryos from temperature fluctuations and ultraviolet radiation (Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, females living in higher-altitudes must store enough energy during the short activity period in order to survive the harsh and extended winter, which may become more difficult for larger individuals. Therefore, Chen et al (2013) 4 suggested that larger females at high altitudes may be costly.…”
Section: Discussionmentioning
confidence: 99%